Workshop Teknik Dasar Fotografi Studio Untuk Komunitas KEK SMA Masehi 1 PSAK Semarang - Setyanto, Daniar Wikan; Noviani, Lusi (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2024)
The Covid-19 pandemic that occurred in the 2020-2022 period has affected teaching and learning activities at SMA Masehi 1 PSAK Semarang, especially in the Photography Extra-Curricular Activity (KEK) Community. Even though the pandemic has ended, the limited face-to-face access at that time and the lack of photography infrastructure have eliminated many students' opportunities to experience photography practicum directly. To overcome this problem, a Basic Photography Studio Techniques Workshop is proposed which will be led by experienced speakers. The workshop aims to provide basic understanding and skills in studio photography, with a focus on the use of lighting equipment. It is hoped that this activity can increase student competence in the creative photography industry and produce quality works. The workshop material in this service includes the material presented including an introduction to flash meters, an introduction to studio lighting softbox accessories, basic single lighting techniques (one light), and basic double lighting techniques (two lights). With this workshop, participants can practice basic Studio photography techniques and can understand the basic theory of flash light measurement in various real cases that can be found in the field.